Hybrid security in AOMDV routing protocol with improved salp swarm algorithm in wireless sensor network - Yousif Hardan Sulaiman; Sami Abduljabbar Rashid; Mustafa Maad Hamdi; Zaid Omar Abdulrahman Faiyadh; Abdulrahman Sabah Jaafar Sadiq; Ahmed Jamal Ahmed (Institute of Advanced Engineering and Science, 2022)
During these years the current trends shows a fast expansion in the field of wireless sensor network (WSN) based applications. Due to this much vulnerability are created and also coverage optimization becomes essential to improve overall performance. However, maximum of the model concentrates only on security or efficiency. In order to create a highly efficient protocol both concepts need to get concerted. So, we developed a protocol namely hybrid security in ad-hoc on-demand multipath distance vector (AOMDV) routing protocol with improved salp swarm algorithm (HSA-ISSA). This model is sub-divided into three sections. They are, wormhole attack and gray hole attack construction AOMDV protocol, improved salp swarm algorithm (SSA) model is used for weighted distance position updates which leads to improve the efficiency. And to secure the network from attacks we use hybrid security with the help of Diffie-Hellman key interchange algorithm and elliptic-curve cryptography (ECC) algorithm. During performance evaluation the proposed HS-ISSA protocol provide stable results in terms of message success rate (MSR), end to end delay (E2E_Delay), network throughput (NT), and average energy efficiency (AEE). Our HAS-ISSA protocol outperformed all the other earlier works by providing hybrid security, optimized coverage as well as energy efficiency to the wireless sensor networks.